Depth-dependent self-healing capacity and mechanism of cracked fiber-reinforced concrete by bacterial community - Xiang, Junchen (2024)
The utilization of bacteria to facilitate the healing of engineered cementitious composites (ECC) has been an interesting approach. However, the commonly used microorganism has been the Bacillus strain, effective in forming bacterial calcium carbonate well at crack top surface but is less favorable for deep-crack healing due to its aerobic nature. In this study, a novel method was introduced that incorporated bacterial community to enhance the self-healing behavior along the depth, breaking away from the traditional single bacteria pattern. The depth-dependent healing ratio of for tire polymer (TP) fiber reinforced ECC using bacterial community (i.e., multiple strains mainly including 15 types of bacteria) was investigated. Healing behaviour was comprehensively evaluated in terms of crack-depth healing, water absorption ratio, and axial strength recovery. Micro-quantitative and macro-quantitative analysis of bacterial products at different depths and the entire crack were conducted through mapping and thermogravimetry. The results revealed the self-healing mechanisms and superiority of the TP-ECC with the bacterial community. Along the crack depth, the healing behaviour of TP-ECC incorporating bacterial community was superior to that of the traditional single bacteria approach. Bacterial communities had an advantage in axial tensile strength recovery compared to single bacteria. It was proved to be technically feasible to enhance self-healing capacity of the TP-ECC when incorporating a bacterial community.